Breakfast Habits, Sleep Quality, and Menstrual Duration as Determinants of Anemia in Adolescent Girls - Asnir, Juliasty; Rakhman, Aulia; Nadila, Devi; Hijra; Abdul Fandir; Rahmawati, Reny (Medicor : Journal of Health Informatics and Health Policy, 2025)
The prevalence of anemia among adolescent girls in the working area of Wani Public Health Center, Donggala District, remains relatively high, reaching 49.2% in 2024. Several contributing factors include poor breakfast habits, poor sleep quality, and abnormal menstrual duration. This study aims to examine the association between breakfast habits, sleep quality, and menstrual duration with the incidence of anemia among adolescent girls. This study highlights the combined role of lifestyle factors (breakfast and sleep quality) and biological factors (menstrual duration) in relation to anemia, which has been scarcely explored in this setting. This research employed a cross-sectional design with a quantitative approach. The study population included all female students in the working area of Wani Public Health Center (n = 81). A total of 68 respondents were selected using the Slovin formula and purposive sampling technique. Data were analyzed using univariate and bivariate analysis with the chi-square test at a significance level of α = 0.05. The findings revealed significant associations between breakfast habits and anemia (p = 0.000), sleep quality and anemia (p = 0.000), and menstrual duration and anemia (p = 0.000) among adolescent girls. Breakfast habits, sleep quality, and menstrual duration are significantly associated with incidence anemia among adolescent girls. These findings provide a basis for preventive efforts through nutrition education, improvement of sleep quality, and monitoring of menstrual health among adolescents.